Tradisi Diskursif Muhammadiyah pada Kritik Maulid - Muhammad As'ad (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2017)
This paper seeks to find the change of the stand of the Muhammadiyah on the practice of the maulid celebration. It will observe through the publication of the Muhammadiyah especially its monthly magazine of Suara Muhammadiyah. In addition, this paper will also use some opinions of the early scholars of the Muhammadiyah in the same topic. To analyse the change, this paper will use the proposed analysis of Talal Asad of discursive tradition. In the conclusion, the paper determines that the change of the stand of the Muhammadiyah on the maulid is influenced by several factors especially the dominant political and power relations in specific time and place which determine the discourse of the maulid criticism of the Muhammadiyah.Key Word : Discursive Tradition, Maulid Criticism